COALITIONS MODEL IN INDONESIAN PRESIDENTIAL SYSTEM - Dinoroy Margonda Aritonang (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractThe option to pick a suitable governmental system is greatly determined by political stability and effectivity considerations. Presidential system used in Indonesian constitutional system is designed along with the format of multiparty which highly requires coalitions among political parties in the parliament. This feature is actually an original or a real character of parliamentary system. It stems from and is developed well in the system. In this article, it will be described the problems based on empirical experiences of Indonesian Presidential cabinet which is struggling with the multiparty system.IntisariPemilihan model pemerintahan amat ditentukan oleh pertimbangan terhadap stabilitas dan efektiftas dari pemerintahan. Sistem Presidensil yang diterapkan di Indonesia didesain dengan format multiapartai, yang amat menghendaki koalisi dalam partai politik di parlemen. Ciri ini sebenarnya amat cocok (lahir dan tumbuh subur) dalam sistem parlementer. Dalam tulisan ini dideskripsikan mengenai problematika yang berangkat dari pengalaman empiris cabinet pemerintahan yang telah berlangsung di Indonesia dalam desain presidensil yang multipartai.